Copredication and Complexity Revisited: Reply to Murphy's Reply. Issue 2 (5th February 2023) - Michel, Christian; Löhr, Guido
Abstract: In Löhr and Michel (2022), we proposed a neurocognitive model within the predictive processing paradigm for acceptability intuitions about copredication sentences. We also addressed "predicate order effects, " the phenomenon that the acceptability of copredication sentences can vary with the order in which the predicates occur. We discussed Murphy's interpretation of order preferences based on a hierarchy of semantic complexity and tried to motivate that other interpretations are worthwhile pursuing. In a reply letter, Murphy (2022) takes issue with our approach, putting forward several purported methodological and conceptual issues with our paper. In this reply, we first clarify where exactly we agree and disagree. Second, we focus on a crucial equivocation and some misrepresentations of our proposal by Murphy.